2021
DOI: 10.2147/jbm.s271478
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Ordering Hypercoagulability Work-Up at an Academic Medical Center

Abstract: Background Venous thromboembolism is a significant clinical event, with an annual incidence of 1–2 per 1000 population. Risk factors include recent surgery, prolonged immobility, oral contraceptive use, and active cancer. Inherited risks include protein C and S deficiencies, antithrombin deficiency, factor V Leiden mutation and prothrombin. These factors can be tested to guide therapy, but current evidence suggests that testing for inherited thrombophilia is not recommended in most inpatient setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Despite these differences and inclusion of patients with any reason for referral for thrombophilia testing, the prevalence of thrombophilia in our study (34 %) aligned well with that in other European and US studies, in which hereditary thrombophilia was confirmed in about a third of the patients with VTE [43,44]. Adherence to thrombophilia guidelines has been investigated in acute in hospital care and other departments than hematology [17,19,20,[44][45][46] and was found to be poor. To our knowledge, this is the first study reporting data from a tertiary hematology center comprising all types of indications for consultation.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Despite these differences and inclusion of patients with any reason for referral for thrombophilia testing, the prevalence of thrombophilia in our study (34 %) aligned well with that in other European and US studies, in which hereditary thrombophilia was confirmed in about a third of the patients with VTE [43,44]. Adherence to thrombophilia guidelines has been investigated in acute in hospital care and other departments than hematology [17,19,20,[44][45][46] and was found to be poor. To our knowledge, this is the first study reporting data from a tertiary hematology center comprising all types of indications for consultation.…”
Section: Discussionsupporting
confidence: 84%
“…Testing was not performed or missing for factor V Leiden mutation (6 %), prothrombin G20210A mutation (13 %), antithrombin (20 %), protein C (30 %), protein S (29 %), antiphospholipid syndrome (11 %). more frequently included patients with pre-existing co-morbidities or major risk factors than our study [5,17,41]. Differences between patient characteristics can likely be explained by different settings, because patients in our study were selected and referred by general practitioners or other specialists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with previous published retrospective studies that demonstrated inappropriate testing. 1,7,8 The American Heart Association (AHA) has published guidelines that outline risk factors to help determine whether an event is provoked by a transient risk factor, due to permanent risk factors or unprovoked. Risk factors include major surgery, trauma, spinal cord injury, bed rest, malignancy, oral contraceptives, hormone replacement therapy, pregnancy, age, obesity, congestive heart failure, previous thromboembolism and thrombophilia.…”
Section: Discussionmentioning
confidence: 99%